Avaliação da distribuição de empreendimentos potencialmente poluidores e do uso de mapas de áreas prioritárias, no processo de licenciamento ambiental do Estado de São Paulo, entre os anos de 2000 e 2015 - Galbiati, Lígia Amoroso (Universidade Federal de São Carlos, 2017)
The loss of biodiversity is one of the worst crises in the current world. Brazil is responsible for the management of a high biodiversity; the Brazilian State recognizes the value of this diversity and tries to preserve it through environmental legislation. Starting with the Law 6.938 / 1981 (the National Environment Policy - NEP) Brazil established legal and technical instruments that help to control environmental impacts resulting from anthropic activities. In a context of high biological diversity living side by side with economic activities of high environmental impact, and after more than three decades of establishing the NEP, this research has proposed to evaluate how the environmental licensing process dialogues with other NEP instruments, among them, the determination of priority areas for conservation in the State of São Paulo. To do so, a survey of Environmental Impacts Assessment (EIA) submitted to the Environmental Company of the State of São Paulo (CETESB) between 2000 and 2015 was carried out and the location of the proposed enterprises and their distribution in the state of São Paulo was evaluated. We also evaluated how much these enterprises have overlapped priority areas for conservation in the State. During the survey, 370 EIAs were submitted, the majority presented between 2007 and 2010, from which 254 were approved. The alcohol and sugar mills were the most numerous enterprises, followed by utilities, housing estates and mining enterprises. It was possible to obtain the geographic coordinates of 168 enterprises, and distribution patterns were found according to the type of activity, with alcohol and sugar mills occupying the center/north of the State, utilities with less aggregate distribution, housing in the metropolitan region of São Paulo and the mining activities are located more to the southeast of the State.The distance of natural resources varied according to the type of enterprise, with an average of 1322 meters of water resources, 834 meters of remaining forest and 15,867 meters of Conservation Units. Through the analysis of the enterprise overlapping priority areas for conservation, it was verified that even after the publication of the maps and their reception by the legislation, 19 presented intention to be installed in these areas. In the analysis of the EIA and the processes of request of Previous License, it was observed that the maps have been mentioned, nevertheless, the context of use is, in general, directed to the environmental compensation and mitigation of impacts, and not for prevention of the possible damages arising from the installation of these ventures in these areas. The distribution pattern of the projects, their proximity of natural resources and the overlapping with priority areas, in the context of high degradation of the ecosystems of the State of São Paulo, demonstrates the need to give greater importance to the cumulative effects of the projects and the analysis of locational alternatives in EIAs to support the decision-making process. The high rate of prior license issuance indicates that the licensing process is still flawed and relies heavily on the prospect of mitigation and compensation for damages rather than preventing them from happening,
Keywords: Avaliação de impacto ambiental; Licenciamento ambiental; Áreas prioritárias para conservação; CETESB; Estudos de impacto ambiental; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE DO PROCESSO DECISORIO